Análise do comportamento na área clínica no Brasil: uma análise com base em publicações - Niero, Carolina Beatriz Ferreira (2011)
This study aimed to analyze published studies in behavior analysis in the clinical area in Brazil, in order to characterize the evolution of this area. The data for this characterization were taken from a journal and two collections of behavioral approach, as well as two non-specific journals in the area. They are: Revista Brasileira de Terapia Comportamental e Cognitiva (RBTCC); Sobre Comportamento e Cognição (SCC); Ciência do Comportamento: Conhecer e Avançar: Psicologia: Teoria e Pesquisa; e Temas em Psicologia. The selection of articles/chapters to be analyzed is given based on a set of keywords that the área encopassed clinical and behavioral approach. A more general characterization of the first publications on clinical behavior analysis was based on all articles/chapters of the selected publications, and a more specific characterization used the articles from the journals: Revista Brasileira de Terapia Comportamental e Cognitiva (RBTCC); Psicologia: Teoria e Pesquisa; e Temas em Psicologia. Through analysis of 337 articles/chapters found in the period 1991 to 2010, it was possible to observe the growing number of publications on clinical behavior over the years. This growth was largely driven by two vehicles of the behavioral approach: the collection, Sobre Comportamento e Cognição and the journal Revista Brasileira de Terapia Comportamental e Cognitiva (RBTCC), whose publication marks the beginning of early stages of growth in the volume of published texts in the area. In relation to the authors, it was possible to identify a small group which wasresponsible for the development of publications of the clinical area in Brazil, concentrating most of the production of the área. Among the topics covered in the articles analyzed, the subject verbal behavior seems to have gained the interest of authors in the area, as well as those involving psychiatric disorders and diseases, and therapeutic relationship. An analysis of the references of the selected articles allowed to emphasize the journals: Temas em Psicologia and Psicologia: Teoria e Pesquisa, which were responsible for the publication of articles of great use in the clinical area, as well as international journals: Journal of Applied Behavior Analysis, o Journal of Consulting and Clinical Psychology e o Behavior Therapy. Even through the analysis of references, it is remarkable the influence of B. F. Skinner and authors such as Robert Kohlenberg and Steven Hayes, who proposed the model of therapy: Functional Analytic Psychotherapy and Acceptance and Commitment Therapy